2013 IEEE International Geoscience and Remote Sensing Symposium - IGARSS 2013
DOI: 10.1109/igarss.2013.6723794
|View full text |Cite
|
Sign up to set email alerts
|

An automated statistical analysis approach to noise reduction for photon-counting lidar systems

Abstract: Satellite-based and airborne lidar instrumentation has been demonstrated to be a strategic tool in increasing our understanding of Earth's polar cryosphere, specifically that of total mass balance, which is a significant factor in estimating sea level rise due to climate change. The Ice, Cloud and land Elevation Satellite 2 (ICESat-2) will provide accurate estimates of local glacial topographical changes with increased measurement precision and change detection capability. Measurements obtained from the airbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The main purpose of the preprocessing is to decrease the number of background photons and to reduce the amount of calculation needed in the subsequent steps. Image processing [25,28,29], envelope curves [26], and histogram statistics [26,[30][31][32][33] are the commonly used methods in the preprocessing step. 1) Image processing: The first preprocessing method involves rasterizing the profile point cloud along the orbit into a 2D image according to the density of the photons.…”
Section: A Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose of the preprocessing is to decrease the number of background photons and to reduce the amount of calculation needed in the subsequent steps. Image processing [25,28,29], envelope curves [26], and histogram statistics [26,[30][31][32][33] are the commonly used methods in the preprocessing step. 1) Image processing: The first preprocessing method involves rasterizing the profile point cloud along the orbit into a 2D image according to the density of the photons.…”
Section: A Preprocessingmentioning
confidence: 99%
“…In some studies, this method has also been directly used to detect the surface, without other subsequent steps. In 2013, Horan et al [33] divided the photons into along-track distance segments containing the same number of photons, and counted the number of photons in each specific elevation range bin. In this method, the photons within an elevation threshold are considered as surface photons, and the elevation threshold is set to a certain elevation range above and below the elevation corresponding to the maximum number of photons.…”
Section: Subsequent Processingmentioning
confidence: 99%
“…Photon-counting technology provides many advantages over conventional linear-mode LiDAR systems [11] but also introduces new challenges for discriminating true returns from the photon-counting point cloud due to a significant number of solar noise photons and system dark current returns [12]. Therefore, an effective approach is necessary to filter the photon-counting data and extract accurate topographic models.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated noise filtering techniques for simulated ICESat-2 [12] and MABEL data [13]. In this letter, a clustering method is modified and used for the detection of the ground surface and vegetation canopy in photon-counting laser altimeter data.…”
Section: Introductionmentioning
confidence: 99%